Effect of danhong injection on the mobilisation of endothelial progenitor cells to vascular repair after percutaneous coronary intervention: a randomised controlled trial. (October 2016) - Hu, Zhen; Wang, Hong; Fan, Guanwei; Zhang, Han; Wang, Xiaoying; Mao, Jingyuan; Zhao, Yingqiang; An, Yi; Huang, Yuhong; Li, Chuan; Chang, Lianying; Chu, Xianming; et al.
Abstract: Background: Endothelial progenitor cells (EPCs) derived from bone marrow are associated with the repair of vascular injury by accelerating re-endothelisation, and represent a potential therapeutic target for ischaemic disease. Danhong injection (DHI), a Chinese Materia Medica standardised product extracted from Radix Salvia miltiorrhiza and Flos Carthamus tinctorius L, is effective in the treatment of ischaemic heart disease. We assessed the effect of DHI on the mobilisation of EPCs and vascular repair mediated by EPCs after percutaneous coronary intervention (PCI). Methods: In a prospective, randomised clinical trial (ChiCTR-ONRC-14004100), patients with coronary heart disease and chest pain (n=54) who were referred to coronary angiography and underwent PCI were enrolled; 12 dropped out because of incomplete blood sample collection. The remaining 42 patients (age 35–75 years) were randomly assigned by random number table method to either a control group (14 men, seven women) that received standard medical treatment or a DHI group (14 men, seven women) that received standard medical treatment combined with DHI (40 mL per day) for 7 days at the affiliated cardiovascular hospital of Qingdao University. The primary outcomes were endothelial lesion and endothelial regeneration. Endothelial lesion was assessed by enumeration of CD45– CD146+ KDR+ circulating endothelial cells (CECs) and inflammatory factors (interleukin 6, C-reactive protein [CRP], tumour necrosis factor α [TNFα]). Endothelial regeneration was evaluated by measurement of CD45dim CD34+ KDR+ EPCs, as determined by flow cytometry. Measurements were taken before PCI, 1 day after PCI, and 7 days after treatment by two investigators masked to treatment assignment. All healthy participants and those with coronary heart disease gave informed consent to participate in the study. All protocols were approved by each of the local ethics committees. Findings: Baseline cytokines, CECs, and EPCs did not differ between DHI and control groups. PCI increased interleukin 6 (p=0·004 in control group; p=0·045 in DHI group), TNF α (p=0·001 in control group; p=0·16 in DHI group), and CECs concentrations (p=0·008 in control group; p=0·005 in DHI group), whereas EPCs decreased (p=0·002 in control group; p=0·001 in DHI group). Compared with the control group, the mean expression levels of cytokines were significantly reduced (interleukin 6 14·98 pg/mL [SD 13·51] vs 7·25 pg/mL [8·03], p=0·001; TNFα 594·17 pg/mL [368·34] vs 388·48 pg/mL [210·24], p<0·0001; CRP 38·07 ng/mL [18·93] vs 22·42 ng/mL [5·94], p=0·04), and CECs were significantly reduced (0·1228% of PBMC [0·0669] vs 0·0564% of PBMC [0·0445], p<0·0001). EPC population significantly increased (0·0962% of PBMC [0·044] vs 0·2569 of PBMC [0·1215], p<0·0001) in DHI group after treatment. Interpretation: These initial results suggest that DHI is effective in improving endothelial repair and protecting the endothelial lesion by mobilising EPCs, by inhibiting the inflammatory response, and by inhibiting of shedding of endothelial cells after PCI in patients with coronary heart disease. Funding: China National Basic Research Program (973 programme, number 2012CB518404).